To read on-screen or printed texts? A quantitative study into EFL students’ reading achievement - Andri Jamaul Rifiyani; Diah Retno Widowati; Dzurriyyatun Ni'mah; M. Faruq Ubaidillah (Association for Scientific Computing Electrical and Engineering(ASCEE), 2022)
The aim of this study was to compare the EFL students’ reading achievement between reading on screen and printed text. This study used a quantitative research design. The participants of this study were 60 students from two classes who took an English education major. The students were randomized into two groups. The experimental group read on screen and the control group read on printed text. The instrument of this study was a news article with 10 multiple choice questions and 10 true-false statements adopted from Breaking News English with the title “Dietary Supplements” by Sean Banville. To analyze the data, the researchers used Independent Sample T-test. The findings revealed a significant difference in students’ reading achievement based on the mean score of both groups. The mean score of the experimental group was 85.33 while the mean score of the control group was 75.00. Then, the result of Sig. (2-tailed) value showed that p value, 0.008, was lower than α 0.05, (0.008 0.05). Hence, it can be concluded that the EFL students who read on screen scored higher in reading achievement than the EFL students who read printed text. The overview of this current study on reading theory, media used, the material given, and reading screen versus paper research, may enable to help teachers and lecturers to make a consideration for their teaching reading in the classroom.